Tinjauan Pemungutan Pajak Pertambahan Nilai Atas Perdagangan Melalui Sistem Elektronik Domestik dan Asing - Ronaldi Marbun; Ning Rahayu (Owner : Riset dan Jurnal Akuntansi, 2023)
The rapid development of the globalization era demands that everyone and their environment create a breakthrough in the form of sophisticated technology to compete and survive in a fairly high economic competition. For entrepreneurs, technology can be used to innovate and advance their businesses to survive and achieve optimal profits. One form of technological innovation, especially the internet, is e-commerce. This activity is carried out online anywhere, borderless, and often called trading through electronic systems (Perdangangan Melalui Sistem Elektronik, PMSE). The rise of transactions in the form of purchases of digital products and services from traders or trade organizers through electronic systems requires the government to issue tax regulations, namely the Regulation of the Minister of Finance number 48 / PMK.03 / 2020, which aims to save the economy by expanding the tax base and promoting equality in taxpayer treatment. This ruling is a derivative regulation of Article 6 paragraph 13a of the Government Regulation in Lieu of Law (Perppu) number 1 of 2020. The regulation of the Minister of Finance number 48/PMK.03/2020 emphasizes the implementation of VAT on PMSE to promote tax justice and accommodate the shift from a conventional to a digital economy. However, in its implementation, there are certainly many challenges faced by tax administrators, VAT collectors appointed to collect VAT on PMSE, and taxpayers as VAT bearers.